Intracerebral Implantation of Autologous Peripheral Blood Stem Cells in Stroke Patients: A Randomized Phase II Study. Issue 12 (December 2014) - Chen, Der-Cherng; Lin, Shinn-Zong; Fan, Jia-Rong; Lin, Chen-Huan; Lee, Wei; Lin, Chao-Chun; Liu, Yi-Jui; Tsai, Chon-Haw; Chen, Jui-Cheng; Cho, Der-Yan; Lee, Chau-Chin; Shyu, Woei-Cherng
In our previous study, intracerebral implantation of peripheral blood stem cells (PBSCs) improved functional outcome in rats with chronic cerebral infarction. Based on this finding, a randomized, single blind controlled study was conducted in 30 patients [PBSC group ( n = 15) and control group ( n = 15)] with middle cerebral artery infarction confirmed on a T2-weighted MRI 6 months to 5 years after a stroke. Only subjects with neurological deficits of intermediate severity based on the National Institute of Health Stroke Scale (NIHSS; range: 9–20) that had been stable for at least 3 months were enrolled. Those in the PBSC group received subcutaneous G-CSF injections (15 μg/kg/day) for 5 consecutive days, and then stereotaxic implantation of 3–8 × 10 6 CD34 + immunosorted PBSCs. All 30 patients completed the 12-month follow-up. No serious adverse events were noted during study period. Improvements in stroke scales (NIHSS, ESS, and EMS) and functional outcomes (mRS) from baseline to the end of the 12-month follow-up period were significantly greater in the PBSC than the control group. The fiber numbers asymmetry (FNA) scores based on diffusion tensor image (DTI) tractography were reduced in every PBSC-treated subject, but not in the control group. Reduction in the FNA scores correlated well with the improvement in NIHSS. Furthermore, a positive motor-evoked potential (MEP) response by transcranial magnetic stimulation (TMS) appeared in 9 of the 15 subjects in the PBSC group. This phase II study demonstrated that implantation of autologous CD34 + PBSC was safe, feasible, and effective in improving functional outcome.